EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN QUIZIZZ TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDK SANTO YOSEPH 3 - Andriyani A.D. Lehan; Netty E.A. Nawa; Mariana Bellanita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the effectiveness of using quizizz learning media on the learning outcomes of class V students at SDK Santo Yoseph 3. This research uses experimental research with a quantitative research approach. This research is a type of Pre-Experimental Design research with One Group Pretest Posttest Design. Data collection in this research was carried out through learning outcomes tests in the form of comprehension tests (pre-test and post-test). The results of research conducted by researchers show that the data in this study is normally distributed. This is proven by the normality test, the Sig value on Shapiro Wilk for Pretest data is 0.335 > o,o5 and Posttest data is 0.300 > 0.05. Then the Quizizz learning media is also effective in improving student learning outcomes. This is proven by the N-Gain test and the mean N-Gain value obtained is 0.70, indicating that the average increase in the measured variable (N-Gain) is in the high category according to the predetermined criteria. So it can be concluded that the use of quizizz learning media is effective in improving the learning outcomes of class V students at SDK Santo Yoseph 3.